Export promotion programs and firm performance: Linking knowledge, commitment, and market strategy to enhance competitiveness - Unggul Heriqbaldi; Miguel Angel Esquivias; WeeYeap Lau; Audrey Friska Cesilia (Journal of Open Innovation: Technology, Market and Complexity)
This study examines the association between export promotion programs (EPPs) and export knowledge, commitment, and management perception, examining their relationship with export strategy, competitiveness, and performance, especially for firms in international markets. Using data collected from 287 Indonesian firms and analyzed using structural equation modeling (SEM), the results show that the export promotion programs are significantly linked with export knowledge and management perception, which are associated with enhanced commitment to global activities. Accordingly, export strategies and competitiveness also show a positive relation, signaling superior performance in exports. The findings highlight the potential role of government support in facilitating global market engagement and identifies key aspects that may help companies succeed in international markets. Companies are encourage to invest more in crucial export resources and knowledge development and build expertise and connections with global markets to facilitate strategic development. Additionally, open innovation is proposed as a potential mechanism through which government and firms can leverage to enhance assistance, knowledge, capabilities, and strategy. Open innovation may potentially enhance firms' capabilities to absorb external knowledge, such as that provided by EPPs, leverage management experience, refine market strategies, and deliver competitive exports.